Slide member and manufacturing method thereof
The sliding member with a soft metal layer and coarse crystals addresses the increased load and harsh environment challenges in automobile engine bearings by forming oil reservoirs for low friction performance.
Patent Information
- Application Number
- JP2020204627
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-09
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2040-12-09
AI Technical Summary
Automobile engine bearings face increased load and harsh environments due to downsizing and turbocharging, requiring improved fatigue resistance, seizure resistance, and low friction properties.
A sliding member with a soft metal layer featuring coarse crystals on its surface, where the coarse crystals have a particle length of 1.5 μm or more and a distribution ratio of 5-50%, which desorb to form oil reservoirs and maintain low friction characteristics.
The described sliding member achieves low friction properties by forming oil reservoirs on the surface, effectively retaining lubricating oil and maintaining smooth sliding even after the resin layer wears off.
Smart Images

Figure 0007656392000005 
Figure 0007656392000006 
Figure 0007656392000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an improvement in a slide member and a manufacturing method thereof. [Background technology]
[0002] A sliding member generally comprises a base layer and a surface layer, and the surface layer supports a sliding member. The surface layer may be entirely or partially formed by plating using a soft metal material. In such a sliding member, Patent Document 1 proposes a material for forming the soft metal layer in which crystal grains of a soft material having a particle size of 0.1 μm to 1 μm are aggregated into a mass shape. A plating layer having fine crystal grains is also disclosed in Patent Document 2. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. WO2017 / 094094 [Patent Document 2] JP 2003-156045 A Summary of the Invention [Problem to be solved by the invention]
[0004] As disclosed in Patent Document 1, when a plating layer having relatively fine crystal grains is used as a soft metal layer, when its surface is used as a sliding surface, the coating strength is improved and high fatigue resistance is provided due to the Hall-Petch relationship. In recent years, due to growing environmental awareness and legal regulations, automobile engines have been developed to be more fuel-efficient, with hybrid systems, idling stop systems, and lighter engines through downsizing. Downsizing of turbocharged engines reduces the size of the engine while maintaining the same power performance as conventional engines, and the shaft diameter and metal width are reduced. As a result, bearings for automobile engines tend to be used in harsher environments than before, with the load increasing compared to conventional ones, and low friction characteristics are also required. [Means for solving the problem]
[0005] One method for ensuring low friction characteristics is to form an oil film at the interface between the sliding surface and the slidable surface. The inventors have investigated how to avoid the loss of the oil film at the interface between the sliding surface and the slidable surface by providing an oil reservoir on the surface of a soft metal layer when the surface of the soft metal layer is used as the sliding surface, thereby ensuring a low friction state between the two.
[0006] Therefore, in this invention, when the surface of a soft metal layer is used as a sliding surface, the idea is to make some of the crystals appearing on this surface large crystals (coarse crystals), and by detaching these coarse crystals from the surface, to form an oil pool in their place. The first aspect of the present invention is defined as follows: A sliding member having a soft metal layer formed by laminating soft metal crystals, Coarse crystals are exposed on the surface of the soft metal layer, The coarse crystals have a particle length of 1.5 μm or more in the planar direction of the surface, and the distribution ratio of the coarse crystals is 5 to 50%.
[0007] The distribution ratio here refers to the ratio of the circumscribing rectangle to the coarse crystals appearing in the cross section of the soft metal layer, with the upper side of the circumscribing rectangle being parallel to the surface reference line of the soft metal layer, and an imaginary straight line passing through the circumscribing rectangle in the cross section and parallel to the surface reference line, and the ratio of the circumscribing rectangle to the unit length of this imaginary straight line, where the surface reference line is the average height of the surface of the soft metal layer appearing in the cross section.
[0008] In the sliding member thus defined, since the coarse crystals are exposed on the surface of the soft metal layer, as the sliding time progresses, the coarse crystals separate and fall off from the sliding surface, and the recesses formed in their places become reservoirs for the lubricating oil. In order for the recesses to function effectively as oil reservoirs, each recess needs to have a certain volume, and the proportion of the recesses relative to the entire surface of the soft metal layer that forms the sliding surface also needs to be controlled.
[0009] Therefore, as shown in the first aspect, the coarse crystals have a grain length of 1.5 μm or more in the planar direction of the surface of the soft metal layer, and thus the volume required for the oil reservoir is secured in the recess formed in the place where the coarse crystals are detached. According to the study by the present inventors, since the coarse crystals also have a certain grain size in the direction perpendicular to the surface of the soft metal layer, by specifying the grain size in the planar direction of the surface, the volume required for the oil reservoir can be secured in the recess formed after the detachment. Crystals with a grain length in the surface direction of less than 1.5 μm will not only have insufficient volume for subsequent recesses, but will also be difficult to detach from the surface, and recesses that can become oil pools may not be formed.
[0010] In addition, as shown in the first aspect, by setting the distribution ratio of the coarse crystals to 5 to 50%, a sufficient amount of recesses is secured on the surface of the soft metal layer after the coarse crystals are detached, and thus the recesses as a whole can hold a sufficient amount of lubricating oil. If the distribution ratio of the coarse crystals is less than 5%, there is a risk that a sufficient amount of lubricant cannot be retained between the surface (sliding surface) of the soft metal layer and the sliding surface of the sliding member. On the other hand, if the distribution ratio exceeds 50%, the smoothness of the surface (sliding surface) of the soft metal layer itself may be impaired, and the friction coefficient may increase.
[0011] The second aspect of the present invention is defined as follows: In the sliding member defined in the first aspect, the distribution rate of coarse crystals is set to 15 to 45%. The sliding member according to the second aspect thus defined ensures low friction characteristics.
[0012] The third aspect of the present invention is defined as follows: In the slide member defined in the first or second aspect, all of the coarse crystals are exposed on the surface of the soft metal layer. According to the slide member of the third aspect thus defined, all the coarse crystals are exposed on the surface of the soft metal layer, so that the coarse crystals can be detached to form oil pools.
[0013] The fourth aspect of the present invention is defined as follows: In a sliding member specified in any one of claims 1 to 3, the distance from the center of gravity of the circumscribing rectangle of the coarse crystal appearing in a vertical cross section of the surface of the soft metal layer, which has the greatest length in the thickness direction of the soft metal layer (hereinafter referred to as the "length in the thickness direction"), to the surface reference line is 25% or less of the thickness of the soft metal layer. In this fourth aspect, the embedding state (buriedness) of the coarse crystals with the longest length in the thickness direction as viewed from the surface of the soft metal layer is specified. That is, by setting the ratio of the distance from the surface of the soft metal layer to the center of gravity of the coarse crystal with the longest length in the thickness direction to the thickness of the soft metal layer to 25% or less, it is shown that the coarse crystals are not deeply embedded in the surface of the soft metal layer, and therefore it is shown that the coarse crystals can be easily detached from the surface. On the other hand, if the length ratio exceeds 25%, it becomes difficult for the coarse crystals to detach from the surface.
[0014] The fifth aspect of the present invention is defined as follows: In the sliding members according to the first to fourth aspects, the soft metal is one or more selected from bismuth (Bi), lead (Pb), indium (In), tin (Sn) and antimony (Sb), or an alloy thereof. The soft metals listed in the fifth aspect are considered to be optimal from an industrial perspective for forming the soft metal layer of the sliding member.
[0015] The sixth aspect of the present invention is defined as follows: In the slide members defined in the first to fifth aspects, a resin layer is further laminated on the soft metal layer. According to the slide member of the sixth aspect thus defined, the properties such as seizure resistance can be improved by selecting the resin constituting the resin layer. Even when the resin layer is laminated on the surface of the soft metal layer, if the coarse crystals are arranged on the surface of the soft metal layer, the coefficient of friction can be prevented from increasing more than the allowable value. Even if the resin layer is partially or entirely worn away and the surface of the soft metal layer is exposed, the coarse crystals in the exposed area are detached and an oil pool is formed there.
[0016] The seventh aspect of the present invention is defined as follows: A method for producing a slide member having a soft metal layer, comprising the steps of: forming a precursor layer by depositing crystals of the soft metal on a surface of a substrate; and a coarse crystal forming step of modifying a part of the crystals constituting the surface of the precursor layer to form coarse crystals, thereby obtaining the soft metal layer. The manufacturing method of the seventh aspect can also be defined as follows: A method for producing a slide member having a soft metal layer, comprising the steps of: forming a precursor layer by stacking columnar crystals of the soft metal on a surface of a substrate; and a coarse crystal forming step of applying stress to the surface of the driving layer to transform part of the crystals and form coarse crystals, thereby obtaining the soft metal layer.
[0017] By carrying out the manufacturing method of the seventh or eighth aspect thus defined, it is possible to manufacture the sliding members defined in the first to sixth aspects. As the coarse crystal formation step of the seventh and eighth aspects, a method of performing shot blasting on the surface of the precursor layer, which is a crystalline laminate of a soft metal, while cooling the surface can be adopted (ninth aspect). As the shot blasting while cooling, wet blasting in which shot material is sprayed together with water can be adopted (tenth aspect). [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a conceptual diagram illustrating the parameters of coarse crystals. [Diagram 2] FIG. 2 is a sectional view showing the configuration of a sliding member according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional photograph of the soft metal layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in further detail below based on the embodiments. The substrate layer constituting the sliding member is generally made of a metal material. In a bearing, which is an example of a sliding member, the substrate layer is configured by laminating a copper-based bearing alloy layer onto a backing layer made of steel, and an intermediate layer made of Ag, Ni, etc. may be formed on the bearing alloy layer. A soft metal layer is laminated on the base layer. Generally, this soft metal layer is formed by plating, but is not limited to plating. As the soft metal, one or more selected from indium (In), tin (Sn), lead (Pb), bismuth (Bi) and antimony (Sb), or an alloy thereof can be used. As the plating method, wet electrolytic plating can be used, but this does not preclude the use of other plating methods.
[0020] When a base layer is plated with these soft metals, the crystals constituting the formed plating layer fall within a predetermined range in size. In the present invention, a layer formed by plating and not subjected to the coarse crystal forming treatment described later is called a precursor layer. The crystal grain size of the soft metal constituting the precursor layer is preferably 1.4 μm or less.
[0021] The grain size was obtained by image processing of the vertical cross section of the precursor layer using the section method. Here, the section method measures the grain size of the grains by dividing the length of a circle formed on the observation image by the number of grains passing through the circle. In the present invention, the grain size was calculated from the length of a circle with a diameter of 2 μm. By adjusting the plating conditions, the crystal structure constituting the precursor layer becomes columnar, with the long axis of the columnar crystal being perpendicular to the surface of the precursor layer.
[0022] When the surface of the precursor layer was subjected to wet blasting, the crystals in the surface layer of the precursor layer were transformed to form coarse crystals. The coarse crystals are presumably formed by the aggregation and fusion of parts of the crystals that make up the precursor layer. In this invention, the precursor layer on which coarse crystals have formed on its surface is called a soft metal layer. The coarse crystals are larger than the crystals that make up the precursor layer. Such coarse crystals are detached from the soft metal layer as the sliding member is used, i.e., as the sliding member slides against the sliding member, progresses.The recesses left behind at the sites of the detached crystals become reservoirs for the lubricating oil.
[0023] For such recesses to function effectively as oil reservoirs, each recess must have a specified volume and be distributed at a constant rate on the surface of the soft metal layer. In the sliding member of this invention, coarse crystals present on the surface of the soft metal layer in a default state (shipped state) are detached during use to form recesses for oil reservoirs, so by specifying the size and distribution rate of the coarse crystals in the default state, the surface state of the soft metal layer in use is indirectly specified.
[0024] <Size of coarse crystals> The coarse crystals 10 have a grain length of 1.5 μm or more in the planar direction of the surface (see FIG. 1). As shown in FIG. 1, the grain length of the coarse crystal 10 is determined by the length of the upper side 100a of a circumscribing rectangle 100 applied to the crystal grain in the cross section of the sliding member. The upper side 100a of this circumscribing rectangle 100 is parallel to the surface reference line S of the soft metal layer 5. Here, the surface reference line S is determined as the average height of the surface of the soft metal layer 5 appearing in the cross section. Since crystals of various sizes appear on the surface of the soft metal layer 5, the surface is microscopically uneven. Therefore, in this invention, the average height of such unevenness (the distance from the central axis C in the case of a cylindrical sliding member) is determined as the surface reference line S. This surface reference line S is also parallel to the central axis C in the cylindrical sliding member.
[0025] It is preferable that the soft metal layer 5 has the following characteristics in the direction perpendicular to its surface. That is, the distance L1 from the center of gravity G to the surface reference line S of the coarse crystal 10 appearing in a vertical cross section of the surface of the soft metal layer 5 and having the greatest length in the depth direction is 25% or less of the thickness L2 of the soft metal layer 5. In Fig. 1, reference numeral 2 denotes a base layer. Since the surface of this base layer 2 is also not flat microscopically, the surface position can be specified by the average height, as with the soft metal layer 5, and the distance between the surface thus determined and the surface reference line S can be determined as the thickness of the soft metal layer 5. The coarse crystals 10 do not penetrate to a depth exceeding ¼ of the soft metal layer 5 from the surface reference line S. This makes it possible for the coarse crystals 10 to be detached from the surface of the soft metal layer 5. In a general-purpose sliding body, the thickness of the soft metal layer 5 is 3 to 20 μm, so that the length in the depth direction of the coarse crystals 10 having the maximum length in the depth direction falls within the range of 0.5 to 10.0 μm.
[0026] <Distribution ratio of coarse crystals> The distribution ratio of the coarse crystals 10 is set to 5 to 50%. The distribution ratio of the coarse crystals 10 is determined as follows. A circumscribing rectangle 100 is applied to the coarse crystals 10 appearing in the cross section of the soft metal layer 5, and the upper side 100a of the circumscribing rectangle 100 is parallel to the surface reference line S of the soft metal layer 5. An imaginary straight line P is formed that passes through all the circumscribing rectangles 100 in the cross section and is parallel to the surface reference line S. The distribution ratio of the coarse crystals refers to the ratio of the circumscribing rectangle to the unit length of this imaginary straight line P, where the surface reference line S is the average height of the surface of the soft metal layer 5 appearing in the cross section.
[0027] The coarse crystals 10 are exposed on the surface of the soft metal layer 5, but because they are particulate, only a portion of the coarse crystals 10 is exposed, and the manner of exposure varies. From the viewpoint of retaining the lubricating oil on the surface of the soft metal layer, the ratio of the recesses that become oil pools to the surface is required, and in this invention, the distribution ratio of the coarse crystals is used as the ratio of the recesses that become oil pools to the surface. This is because the sites where the coarse crystals 10 separate become the recesses that become oil pools. By setting the distribution ratio of the coarse crystals at 5 to 50%, sufficient lubricating oil can be retained at the interface between the surface of the soft metal layer and the sliding surface. It is more preferable that the distribution rate of the coarse crystals is 15 to 45%.
[0028] The coarse crystals 10 were obtained by wet blasting the surface of the precursor layer formed by plating. When the precursor layer is subjected to a general blasting process, the crystals in the precursor layer are generally refined. Furthermore, according to the study by the present inventors, it was found that the grain size of the coarse crystals 10 also changes when the wet blasting conditions are changed. The shot material, water temperature, and shot pressure used in the wet blasting can be selected arbitrarily depending on the material of the precursor layer.
[0029] For example, the shot material may be alumina, glass beads, or other general-purpose shot materials, and the size of the shot material may be of a general purpose type. In the embodiment, the temperature of the water ejected together with the shot material is room temperature, but warm water or cooling water may also be used. The shot pressure is appropriately adjusted depending on the selected precursor layer material and the material and size of the shot material.
[0030] From the above, by performing blasting on the surface of the precursor layer while cooling it, the size and distribution of the formed coarse crystals can be controlled. Although water is used as the coolant in wet blasting, other liquids such as oil or alcohol, or gases such as cold air or water vapor can also be used as the coolant. In other words, it means that stress is applied to the surface of the precursor layer to transform part of the crystals. It is also possible to apply stress to part of the surface by heat or light. EXAMPLES
[0031] An embodiment of the present invention will now be described. The sliding member 1 of the embodiment had a cross-sectional structure shown in Fig. 2, for example. More specifically, a bimetal was manufactured by lining a steel backing layer 3 with a copper-based bearing alloy layer 4, and this bimetal was molded into a semi-cylindrical or cylindrical shape. Thereafter, the surface of the bearing alloy layer 4 was finished by boring. This resulted in the formation of a base layer 2 (thickness: 1.5 mm). Next, the surface of the semi-cylindrical or cylindrical molded product was cleaned (electrolytic degreasing + acid cleaning). The upper surface of the base layer 2 thus obtained was subjected to wet plating to form a plating layer 5 (about 15 μm).
[0032] The plating conditions for forming the plating layer 5 in this embodiment were adjusted so as to obtain the "crystal grain size other than the surface layer" in Table 1 described later. This crystal grain size is equal to the crystal grain size of the crystals constituting the precursor layer. Each crystal had a columnar structure (see FIG. 2). Crystals with the desired grain size can be obtained by adjusting the composition of the plating solution, the stirring method, the temperature, the current density, etc. Those skilled in the art will understand that these specific conditions are not fixed, but are appropriately selected based on the experience of the plating operator.
[0033] The precursor layer of the sample thus obtained was washed by a known method. Next, the surface of the precursor layer was subjected to a wet blasting treatment. The conditions for wet blasting are as follows: Shot material: Alumina #2000~600, glass beads Processing pressure: 0.1 to 0.3 MPa Water temperature: normal temperature
[0034] The specimens after wet blasting are shown in Table 1. [Table 1]
[0035] A schematic diagram of the cross section of the sample of the embodiment is shown in FIG. Reference numeral 10 in the figure denotes coarse crystals, which are formed on the surface of the soft metal layer 5. The lower portion of the soft metal layer 5 is not affected by the wet blasting, and the crystals formed by plating remain in their original state (columnar crystals). When the grain size of such crystals is calculated by the intercept method, the grain size is 1.4 μm or less.
[0036] In Table 1, the "average crystal grain size other than the surface layer" was obtained as follows. The soft metal layer 5 is divided into 5 equal parts in the depth direction, and the intercept method is performed at positions spaced apart in the surface direction from each layer, excluding the layer (surface layer) containing the coarse crystals 10, to calculate the crystal grain size. The average value of the crystal grain size obtained at each position is defined as the "average value of the crystal grain size other than the surface layer." This average value indicates the average value of the crystal grain size of the precursor layer. The "maximum coarse crystal size" was obtained as follows. In the coarse crystals 10 appearing in the cross section of the soft metal layer 5 obtained by cutting the sliding member along the axial direction, the one whose circumscribing rectangle 100 has the longest upper side 100a length is defined as the "maximum coarse crystal," and this length is expressed as the "size."
[0037] The "distribution ratio of coarse crystals" was obtained as follows. A circumscribing rectangle 100 is applied to the coarse crystals 10 appearing in the cross section of the soft metal layer 5. In this case, the upper side 100a of the circumscribing rectangle 100 is parallel to the surface reference line S of the soft metal layer 5. In the cross section, an imaginary straight line P is formed that passes through the circumscribing rectangle and is parallel to the surface reference line, and the proportion of the circumscribing rectangle in a unit length of this imaginary straight line P is defined as the distribution proportion of the coarse crystals. Note that the imaginary straight line P passes through the circumscribing rectangles of all the coarse crystals 10 appearing in the cross section in that unit length. The total width of the obtained image can be used as this unit length.
[0038] In Table 1, the "friction coefficient after 5 hours" was determined by carrying out a friction test under the conditions shown in Table 2. [Table 2] That is, the start and stop were repeated, and the friction coefficient was measured after 5 hours.
[0039] The results in Table 1 reveal the following: It is assumed that samples that can maintain a friction coefficient of 0.20 or less even after 5 hours are deemed to be preferable in terms of low friction. Even if the crystal grain size of the precursor layer is the same, there is a large difference in low friction depending on whether wet blasting is performed or not, i.e., whether coarse crystals are present or not (see Examples 1 to 7 and Comparative Examples 1 and 2). As a result, based on the results of Example 5 and Comparative Example 1, which have the lowest wet blasting energy, it is considered preferable that the size of the coarse crystals (the length in the planar direction of the surface of the soft metal layer) is 1.5 μm or more, and the distribution ratio of the coarse crystals (the ratio of the projected portion of the coarse crystals that appears in the same area on the projection plane at the same distance from the surface when the large crystals are projected onto the surface) is 5% or more.
[0040] Even if wet blasting is performed, if excessive coarse crystals are formed and the distribution ratio of the coarse crystals exceeds 50% (see Example 1 and Comparative Example 3), the low friction property decreases. Furthermore, by comparing Examples 1 and 5 with Examples 2 to 4, it is considered preferable that the distribution ratio of coarse crystals is 15 to 45%. As shown in Comparative Example 2, when the grain size of the crystals constituting the precursor layer of the soft metal layer formed by plating is large to begin with, it cannot be said that the low friction properties are excellent.
[0041] Table 3 examines the thickness (length in the direction perpendicular to the surface) of the coarse crystals, which defines the depth of the recessed portion of the oil reservoir to be formed on the surface of the soft metal layer. [Table 3] In Table 3, the "centre depth" refers to the ratio of the distance L1 from the centre of gravity G of the circumscribing rectangle 100 shown in FIG. As can be seen from the results in Table 3, when heat treatment is performed after wet blasting, the coarse crystals expand preferentially, and the center of gravity position becomes deeper. From a comparison between Example 8 and Example 9, it is preferable that the center of gravity depth is 25% or less.
[0042] The heat treatment here is performed by heating in an electric furnace in the presence of air for 10 to 60 minutes. In the definitions in Table 1, the largest crystal is specified based on the length of the upper side of the circumscribing rectangle. According to the observations of the present inventors, in the circumscribing rectangle applied to the coarse crystal, the one having the maximum length of the upper side also has the maximum length of the side (i.e., in the depth direction of the soft metal layer 5).
[0043] Table 4 examines the low friction properties when a resin layer (containing a solid lubricant) is laminated on the surface of a soft metal layer. [Table 4] The samples in Table 4 were obtained by laminating a resin layer on the soft metal layer 5 of the sliding member shown in FIG. 2. In the samples in Table 4, the resin layer had a thickness of 3 μm, but the resin layer may have a thickness of 2 to 20 μm. In Table 4, the friction coefficient after the resin layer was worn indicates the friction coefficient when a friction test was performed and it was visually confirmed that the resin layer had worn away.
[0044] Even if the surface of the soft metal layer is covered with a resin layer, the stress caused by sliding is applied to the surface of the soft metal layer, so that the coarse crystals are detached and oil-retaining recesses are formed in their places. If the size and distribution rate of such recesses are suitable, a smooth sliding state (low friction coefficient) is maintained between the sliding member and the slidable member even if the resin layer is worn away. This can be seen from the relationship between Examples 12 to 14 and Comparative Examples 4 and 5. In Examples 12 to 14, the distribution rate of the coarse crystals is within 5 to 50%, whereas in Comparative Examples 4 and 5, it is outside the range. Example 14 shows that the above effect does not depend on the type of solid lubricant contained in the resin layer.
[0045] The present invention is not limited to the above-mentioned embodiment. Various modifications within the scope of the claims and within the scope of those skilled in the art are also included in the present invention. A device using a bearing mechanism, such as an internal combustion engine, using the sliding member of the present invention exhibits excellent sliding characteristics. [Explanation of symbols]
[0046] 1 Sliding member 2 Base material layer 3. Backing layer 4 Bearing alloy layer 5 Soft metal layer 10 Coarse crystals 100 circumscribed rectangle 100a Top side of bounding rectangle S surface reference line L1 Length from the center of gravity to the surface reference line L2 Soft metal layer thickness
Claims
1. A sliding member having a soft metal layer formed by laminating soft metal crystals, coarse crystals formed of the soft metal are exposed on the surface of the soft metal layer, The coarse crystals have a particle length of 1.5 μm or more in the planar direction of the surface, and the distribution ratio of the coarse crystals is 5 to 50%. Here, the distribution ratio refers to a ratio of the circumscribing rectangle to the coarse crystals appearing in the cross section of the soft metal layer, with the upper side of the circumscribing rectangle being parallel to a surface reference line of the soft metal layer, and an imaginary straight line passing through all of the circumscribing rectangles in the cross section and parallel to the surface reference line being formed, and wherein the surface reference line is the average height of the surface of the soft metal layer appearing in the cross section, A sliding member, wherein the distance from the center of gravity of the circumscribing rectangle of the coarse crystal appearing in a vertical cross section of the surface, which has the greatest length in the thickness direction of the soft metal layer, to the surface reference line is 25% or less of the thickness of the soft metal layer.
2. 2. The sliding member according to claim 1, wherein the distribution ratio of the coarse crystals is 15 to 45%.
3. 3. The sliding member according to claim 1, wherein all of the coarse crystals are exposed on the surface.
4. The sliding member according to any one of claims 1 to 3, wherein the soft metal is one or more selected from bismuth (Bi), lead (Pb), indium (In), tin (Sn), and antimony (Sb), or an alloy thereof.
5. 5. The sliding member according to claim 1, further comprising a resin layer laminated on the surface of the soft metal layer.
6. A method for producing a slide member according to claim 1, comprising the steps of: forming a precursor layer by depositing crystals of the soft metal on a surface of a substrate; and a coarse crystal forming step of modifying a part of the crystals constituting the surface of the precursor layer to form coarse crystals, thereby obtaining the soft metal layer.
7. A method for producing a slide member according to claim 1, comprising the steps of: forming a precursor layer by stacking columnar crystals of the soft metal on a surface of a substrate; and a coarse crystal forming step of applying stress to the surface of the precursor layer to transform part of the crystals and form coarse crystals, thereby obtaining the soft metal layer.
8. The method according to claim 6 or 7, wherein in the coarse crystal forming step, a surface of the precursor layer is shot blasted while being cooled.
9. The manufacturing method according to claim 8 , wherein the coarse crystal forming step comprises wet blasting a surface of the precursor layer.
10. A method for producing a slide member having a soft metal layer formed by laminating soft metal crystals, comprising the steps of: forming a precursor layer by depositing crystals of the soft metal on a surface of a substrate; a coarse crystal forming step of modifying a part of the crystals constituting the surface of the precursor layer to form coarse crystals, thereby obtaining the soft metal layer, The average grain size of the crystals is 1.4 μm or less, The coarse crystals have a particle length of 1.5 μm or more in the planar direction of the surface, and the distribution ratio of the coarse crystals is 5 to 50%. Here, the distribution ratio refers to a ratio of the circumscribing rectangle to the coarse crystals appearing in the cross section of the soft metal layer, with the upper side of the circumscribing rectangle being parallel to the surface reference line of the soft metal layer, and an imaginary straight line passing through the circumscribing rectangle in the cross section and parallel to the surface reference line being formed, and wherein the surface reference line is the average height of the surface of the soft metal layer appearing in the cross section. A method for manufacturing a sliding member.
11. A method for producing a slide member having a soft metal layer formed by laminating soft metal crystals, comprising the steps of: forming a precursor layer by stacking columnar crystals of the soft metal on a surface of a substrate; a coarse crystal forming step of applying stress to a surface of the precursor layer to transform a part of the crystals to form coarse crystals, thereby obtaining the soft metal layer, The average grain size of the crystals is 1.4 μm or less, The coarse crystals have a particle length of 1.5 μm or more in the planar direction of the surface, and the distribution ratio of the coarse crystals is 5 to 50%. Here, the distribution ratio refers to a ratio of the circumscribing rectangle to the coarse crystals appearing in the cross section of the soft metal layer, with the upper side of the circumscribing rectangle being parallel to the surface reference line of the soft metal layer, and an imaginary straight line passing through the circumscribing rectangle in the cross section and parallel to the surface reference line being formed, and wherein the surface reference line is the average height of the surface of the soft metal layer appearing in the cross section. A method for manufacturing a sliding member.
12. The method according to claim 10 or 11, wherein in the coarse crystal forming step, a surface of the precursor layer is shot blasted while being cooled.
13. The manufacturing method according to claim 12 , wherein the coarse crystal forming step comprises wet blasting a surface of the precursor layer.
14. The method according to claim 10 or 11, wherein the distribution ratio of the coarse crystals in the projection plane is 15 to 45%.
15. 15. The manufacturing method according to claim 10, wherein the distance from the center of gravity of the circumscribing rectangle of the coarse crystal appearing in a vertical cross section of the surface of the soft metal layer, the rectangle having the greatest length in the thickness direction of the soft metal layer, to the surface reference line is 25% or less of the thickness of the soft metal layer.
16. The manufacturing method according to any one of claims 6 to 15, wherein the soft metal is one or more selected from bismuth (Bi), lead (Pb), indium (In), tin (Sn), and antimony (Sb), or an alloy thereof.
17. The manufacturing method according to any one of claims 6 to 16, further comprising the step of laminating a resin layer on a surface of the soft metal layer.
Citation Information
Patent Citations
Sliding member
JP2003156045A
Sliding member
JP2009264441A
PROCESS OF MANUFACTURE OF SLIDE BEARING AND Sn GROUP OVERLAY OF SLIDE BEARING
JP2014081040A
Sliding member and sliding bearing
WO2017094094A1